Edukasi “Isi Piringku” Terhadap Pengetahuan dan Perilaku Pada Ibu Balita Stunting di Maluku - Alisye Siahaya; Rohadi Haryanto; Titin Sutini (FORIKES, 2021)
“Fill My Plate” education was given to improve the knowledge and the action of mother in fulfilling the need of nutriments for the stunting toddlers. The arm of this study wa to know the influence of “Fill My Plate” education toward mothers knowledge and action in fulfilling the need of nutriments for stunting toddlers in Maluku. Methods: This study was an experimental quasy with pre-test and post-test control group design in used sampling total technique with 46 mothers of the entire population. Results: Analyzing through Wilcoxon tes showed there was an influence of “Fill My Plate” education toward mothers knowledge and action in intervention group with p value < 0,05 and there was none of influence of “Fill My Plate” education toward mother knowledge and action in control group with p value >0,05. Conclusion: “Fill My Plate” education could be given for mother who had stunting toddlers, specifically for them who had low education and who were still young, so that it could improve the knowledge as well as the action of mother in fulfilling the need of children’s nutriments Keywords: action; “fill my plate education; knowledge; stunting ABSTRAK Edukasi “isi piringku” diberikan untuk meningkatkan pengetahuan dan perilaku ibu dalam pemenuhan kebutuhan gizi pada balita stunting. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh edukasi “isi piringku” terhadap pengetahuan dan perilaku ibu dalam pemenuhan kebutuhan gizi pada balita stunting di Maluku. Metode: Penelitian ini merupakan penelitian quasy experimental dengan desain penelitian pre-test and post-test control group design. Penelitian ini menggunakan teknik total sampling dengan jumlah keseluruhan populasi yaitu 46 ibu. Hasil: Analisis menggunakan uji Wilcoxon menunjukkan ada pengaruh edukasi “isi piringku” terhadap pengetahuan dan perilaku ibu pada kelompok intervensi dengan p value 0,05. Kesimpulan: Edukasi “isi piringku” ini dapat di berikan kepada ibu yang memiliki balita stunting terutama bagi ibu yang berpendidikan rendah dan relatif masih muda untuk dapat meningkatkan pengetahuan dan perilaku ibu dalam memenuhi kebutuhan gizi anak. Kata kunci: edukasi “isi piringku”; pengetahuan; perilaku; stunting